2021
DOI: 10.7704/kjhugr.2020.0057
|View full text |Cite
|
Sign up to set email alerts
|

Proton-pump Inhibitors and the Risk of Dementia: A Systematic Review and Meta-analysis

Abstract: Background/Aims: Proton pump inhibitors (PPIs) are widely used to treat several acid-related gastrointestinal disorders. This study aimed to investigate the risk of dementia in patients taking PPIs.Materials and Methods: A systematic review was conducted to evaluate the correlation between PPIs and dementia. The methodological quality of the included studies was evaluated using the Risk of Bias Assessment tool for non-randomized studies. Publication bias was assessed.Results: A total of 12 nested, case-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Statistical heterogeneity and small‐study effect are known as two major issues affecting the validity of meta‐analyses 34 . Although heterogeneity in our primary analysis is substantial ( I2 = 99%), it is consistent with the ones from previous meta‐analyses by Wang et al ( I2 = 98.5%), 15 Khan et al ( I2 = 96%), 53 Desai et al ( I2 = 93%) 52 and Yoon et al ( I2 = 91%) 54 . If the studies become very large, the sampling error tends to null and I2 comes close to 1.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Statistical heterogeneity and small‐study effect are known as two major issues affecting the validity of meta‐analyses 34 . Although heterogeneity in our primary analysis is substantial ( I2 = 99%), it is consistent with the ones from previous meta‐analyses by Wang et al ( I2 = 98.5%), 15 Khan et al ( I2 = 96%), 53 Desai et al ( I2 = 93%) 52 and Yoon et al ( I2 = 91%) 54 . If the studies become very large, the sampling error tends to null and I2 comes close to 1.…”
Section: Discussionsupporting
confidence: 89%
“…A recent meta‐analysis with five studies 54 found a pooled HR of 1.17 (95% CI = 0.91; 1.49). The authors assessed the risk of bias of each study using the risk of bias assessment tool for non‐randomized studies (RoBANS) 55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation